A comparative study problems of a Tagalog speaker in learning the use of the English relative pronouns (Nominative case) in adjuncts - Vea, Agnes Banzon 1922- (University of the Philippines, 1964)
This comparative study brings out the problems of a Tagalog speaker learning the use of English relative pronouns (nominative case) in adjuncts through a comparison of this grammatical system with its "corresponding" functional unit in Tagalog. The comparison is based on three linguistic forms: form, meaning, and distribution.